Home Ground Notions Influencing Foochow And Hokkien Speakers’ Language Use In Kuching, Sarawak - Puah, Yan Yann; Ting, Su Hie (2013)
In the past, ethnic groups tend to be concentrated in certain localities and their interactions tend to be within their own group. However, with past migration for educational and career purposes, ethnic groups are now spread all over. Even so, the notion of homeland and home ground are still entrenched in the minds of the people. Specific reference is made to the Chinese sub-groups in Sarawak, and this study focusses on the Foochow whose homeland is Sibu and the Rejang hinterland and the Hokkien whose homeland is Kuching. The study examined the languages used by Foochow and Hokkien speakers in urban Kuching and the reasons for their language choice. A case study was conducted on twenty Chinese residing in Kuching (10 Foochow and 10 Hokkien). The results showed that the Hokkien participants speak Hokkien in the family domain regardless of whether there is intermarriage but the Foochow participants choose Mandarin if their spouse is from other Chinese sub-groups. For interactions with other Chinese, the Hokkien participants’ first choice is Hokkien but the Foochow would only speak Foochow to other Foochow people and use Hokkien and Mandarin with other Chinese. For interethnic interactions, English, Bahasa Melayu and Iban are used. Various reasons for the language choices were reported by the participants but it seems that the most important finding that emerged is that the Chinese sub-groups would speak their dialect only on their “home ground” but when they are on “away ground”, they seek to blend in.